Combining Ti4(embonate)6 anionic cages and π-conjugated coordination cations for highly effective optical limiting - Yuan, Yuan; Dong-Hui, Zhang; Qiao-Hong, Li; Chen, Shu-Mei; Yan-Ping, He; Zhang, Jian (Chemical communications (Cambridge, England), 2024)
The integration of anionic Ti4L6 (L = embonate) cages and π-conjugated coordination cations into ordered structures can produce high-performance nonlinear optical (NLO) materials. More specifically, by employing Ti4L6 cages for assembly with mixed N,N-chelated and P,P-chelated type conjugated organic ligands and Ag+ ions, three cage-based structures have been synthesized and structurally characterized. Among them, an ion pair structure with strong π–π accumulation exhibits a significant third-order NLO response, and an excellent optical limiting effect has been experimentally verified. This work provides a promising material for NLO applications.